Female relative age effects and the second-quartile phenomenon in young female ice hockey players - Hancock, D. J. (Psychology of Sport and Exercise, 2017)
Objectives: Relative age effects exist across sports and cultures (Cobley, Baker, Wattie, & McKenna, 2009), though a recent, unusual trend is females born in the second quartile of the selection year are most over-represented on elite teams. The first purpose of this study was to test the hypothesis that the second-quartile phenomenon was the result of first-quartile female athletes registering to play male sport. Due to the nature of the collected data, a secondary purpose was to examine relative age effects across female age divisions. Design: Cross-sectional, with multiple chi-square analyses. Method: Players included 29,924 female ice hockey players (ages 7-17 years) from the Ontario Hockey Federation. Birthdates were converted into quartiles following the Hockey Canada selection year. Results: Relative age effects (with the second quartile most over-represented) existed for the entire sample , those registered for female ice hockey and those registered for male ice hockeyThe strength of the effect lessened as athletes aged. Conclusion: It appears the second-quartile phenomenon cannot be explained by athletes` choice to play male sport. Further, female relative age effects appear strongest at younger ages. The discussion includes integration of results with previous literature, along with plausible explanations.